Some aspects of circular depressive disorders pathomorphosis at present - N. G. Pshuk; I. S. Pototska; О. О. Belov (Zaporožskij Medicinskij Žurnal)
The article analyzes features of circular depressive disorders socio-demographic and clinical pathomorphosis in period of 1971 to 2016.